Majmūʿa-yi āthār-i ḥājjī ʿAbdallāh Khān Qarāgūzlū Amīr Niẓām-i Hamadānī - Qarāgūzlū, ʿAbdallāh Khān (Miras Maktoob, ISBN: 9789004365452., 2019)
In Persia under the Qajars (1210-1344/1796-1925) tribal leaders played an important role; at the regional level and also in matters of state. An illustrative example is ʿAbdallāh Khān Qarāgūzlū (d. 1334/1916), a prominent member of the Turkish Qarāgūzlū tribe of Hamadan. Qarāgūzlū, who died of a stroke age sixty, had a colourful life. Governor of the district of Astarābād at only 26 years of age, he had a career in which he served in a wide range of military and administrative positions, both regionally and nationally. But like so many others, he was certainly not without blemish: emprisoned on accusations of rebellion, rejected by parliament as governor of Kurdistan on charges of embezzlement and despotism in an earlier office in Shiraz, and an incapable Minister of Finance whose policies were often determined by taking an omen from his prayer beads. In the present collection of notes and reports, the tone is of course more positive.